2004
DOI: 10.1007/s10295-004-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-culture production of blastospores of the bioinsecticidal fungus Paecilomyces fumosoroseus using portable fermentation equipment

Abstract: The production of fungal spores using on-site, non-sterile, portable fermentation equipment is technically constrained. Very little information is available on the production requirements, such as medium concentration, inoculum stabilization, required fermentation times, and maintenance of axenic growth. In this study, we developed a two-part, liquid concentrate of the production medium that remains stable and soluble at room temperature. We also examined inoculum stability and showed that freeze- or air-dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The cost of their production is high because of the risk of contamination and the long culturing time required (up to 4 weeks of growth). Moreover, for solid culturing, large spaces with appropriate facilities and skilled technicians are needed for careful handling of culture bags or trays for suitable aeration . In liquid culturing, the fungi produce blastospores, which are developed from hyphae, and their production is completed in 3–4 days (depending on the culture medium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of their production is high because of the risk of contamination and the long culturing time required (up to 4 weeks of growth). Moreover, for solid culturing, large spaces with appropriate facilities and skilled technicians are needed for careful handling of culture bags or trays for suitable aeration . In liquid culturing, the fungi produce blastospores, which are developed from hyphae, and their production is completed in 3–4 days (depending on the culture medium).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for solid culturing, large spaces with appropriate facilities and skilled technicians are needed for careful handling of culture bags or trays for suitable aeration. 6 In liquid culturing, the fungi produce blastospores, which are developed from hyphae, and their production is completed in 3-4 days (depending on the culture medium). This short production time reduces the risk of contamination and the cost of production.…”
Section: Introductionmentioning
confidence: 99%
“…Jackson, Payne and Odelson (2004) observed that low levels of bacterial contamination in massproduced conidia of another entomopathogenic fungus Isaria (formerly Paecilomyces) fumosoroseus did not cause significant problems. However, as Jenkins and Grzywacz (2000) argued, higher levels of microbial contamination can interfere with, among other things, biopesticide efficacy.…”
Section: Introductionmentioning
confidence: 94%
“…These findings suggest that it may be cost-effective and feasible to use non-sterile equipment in certain botechnology applications in the future. 31 Another illustration of how mobile equipment has become occurred in South Africa in 2003. In 2003, a visiting Danish researcher and two South Africans surprised much of the scientific establishment, the government, and the public with their announcement that they had "cloned a cow" at a relative remote research station using a new, handmade cloning method that used a hand-crancked generator for power.…”
Section: Policy Lesson #5: Covert Biological Weapons Research and Devmentioning
confidence: 99%